Computational and mathematical modeling in the social sciences - De Marchi, Scott (Cambridge ; New York : Cambridge University Press, 2005)
This book provides an overview and a critique of mathematical modeling in the social sciences. It covers the three major traditions: game theory, statistics, and computational modeling.
Includes bibliographical references (p. 181-190) and index.
oif 04/05/15
Loan
Keywords: Social sciences -- Mathematical models